A tellurium nanowire supported noble metal composite material, a preparation method and application thereof

CN118495479BActive Publication Date: 2026-10-16WUYI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410427487.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-10
Publication Date
2026-10-16
Estimated Expiration
2044-04-10

AI Technical Summary

Technical Problem

而现有的技术中,碲纳米线制备方法往往采用易制爆的药品水合肼充当还原剂,实验过程存在安全隐患和对环境造成一定的污染;而具有绿色环保特点的制备方法流程过于复杂,实验环境苛刻,严重影响了推广使用

Benefits of technology

[0013] The preparation method of this invention uses tellurium as an oxidant and carbon as a surfactant, while simultaneously using a combination of carbon and a reducing agent to achieve a reduction effect. The reducing agent is mild, thus preparing the precursor tellurium nanowires for the composite material. In the first mixed solution of this invention, the tellurium source is reduced and self-polymerized to form nanowires under the action of the reducing agent and carbon source. The surfactant and carbon source inhibit the growth of elemental tellurium, preventing the final precursor particles from being too large, thereby effectively generating nanowire materials of uniform length.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004888564570000011
    Figure HDA0004888564570000011
  • Figure HDA0004888564570000012
    Figure HDA0004888564570000012
  • Figure HDA0004888564570000021
    Figure HDA0004888564570000021
Patent Text Reader

Abstract

The application discloses a kind of tellurium nanowire supported noble metal composite materials and preparation method and application, belong to composite material preparation technical field.The preparation method of the composite material of precursor tellurium nanowire includes the following steps: tellurium source, carbon source, reducing agent and first solvent are mixed stirring, heating reaction, separation solid phase, obtain precursor tellurium nanowire;The reducing agent is glycol or sodium citrate.The tellurium nanowire supported noble metal composite material prepared by the application has the characteristics of high conductivity, uniform particle size distribution, large effective specific surface area, can be used in various catalytic fields, and the preparation method is safe and reliable, process condition is simple and easy to control, production cost is low, suitable for industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material preparation technology, and in particular to a tellurium nanowire-supported noble metal composite material, its preparation method, and its application. Background Technology

[0002] Hydrogen energy is an eco-friendly, abundant, cost-effective, and high-energy-density clean energy carrier. Furthermore, its zero-carbon emissions significantly alleviate environmental pressure, making it widely considered the best candidate to replace fossil fuels. Currently, noble metal electrode catalysts remain the most active materials for catalytic hydrogen production via water electrolysis. Pt-based catalysts and Ir or Ru-based catalysts are the most advanced electrocatalysts used in HER and OER, respectively.

[0003] In recent years, ruthenium telluride (Te) has been widely studied as a novel water electrolysis catalyst. Compared with O, S, and Se, Te exhibits more metallic properties, which is more conducive to electron transport in electrocatalysts. Furthermore, compared to chalcogenides, tellurium sources in tellurides have lower toxicity and are safer. Since elemental tellurium tends to form one-dimensional nanowire structures, Te nanowires can be used as templates for reaction products to prepare materials with various linear structures, such as noble metal nanowires and telluride nanowires, to enhance electrocatalytic activity. Therefore, the design and development of tellurium nanowire-supported Ru composite materials has become a research hotspot for the electrocatalytic hydrogen evolution reaction. However, in existing technologies, tellurium nanowire preparation methods often use hydrazine hydrate, a potentially explosive reagent, as a reducing agent, posing safety hazards and causing environmental pollution during the experimental process. Meanwhile, green and environmentally friendly preparation methods are overly complex and require harsh experimental environments, severely hindering their widespread application.

[0004] Therefore, there is a need to provide a tellurium nanowire-supported noble metal composite material with good electrocatalytic performance and a simple and environmentally friendly preparation method to solve the above problems. Summary of the Invention

[0005] This invention aims to at least solve one of the technical problems existing in the prior art. To this end, this invention proposes a method for preparing tellurium nanowire-supported noble metal composite materials. The preparation method is simple and environmentally friendly, and the composite material exhibits good electrocatalytic performance.

[0006] The present invention also provides the above-mentioned tellurium nanowire-supported noble metal composite material.

[0007] The present invention also provides applications of the above-mentioned tellurium nanowire-supported noble metal composite materials.

[0008] A first aspect of the present invention provides a tellurium nanowire-supported noble metal composite material.

[0009] The preparation method of the precursor tellurium nanowires of the composite material includes the following steps:

[0010] Tellurium source, carbon source, reducing agent and first solvent are mixed and stirred, heated to react, and the solid phase is separated to obtain precursor tellurium nanowires;

[0011] The reducing agent is ethylene glycol or sodium citrate.

[0012] The tellurium nanowire-supported noble metal composite material according to the first aspect of the present invention has at least the following beneficial effects:

[0013] The preparation method of this invention uses tellurium as an oxidant and carbon as a surfactant, while simultaneously using a combination of carbon and a reducing agent to achieve a reduction effect. The reducing agent is mild, thus preparing the precursor tellurium nanowires for the composite material. In the first mixed solution of this invention, the tellurium source is reduced and self-polymerized to form nanowires under the action of the reducing agent and carbon source. The surfactant and carbon source inhibit the growth of elemental tellurium, preventing the final precursor particles from being too large, thereby effectively generating nanowire materials of uniform length.

[0014] The preparation method of this invention mainly utilizes a solvothermal uniform reaction method, which eliminates the need for high-temperature heating equipment such as tube furnaces to obtain hollow strip-shaped tellurium nanowire-supported noble metal composite materials. The entire production process is safe and reliable, the process conditions are simple and easy to control, the materials are widely available, and the production process has low energy consumption, making it suitable for large-scale industrial production.

[0015] According to some embodiments of the present invention, the mass ratio of the tellurium source to the carbon source is 1:(1-20).

[0016] According to some embodiments of the present invention, the volume ratio of the first solvent to the reducing agent is 1:(0.25-3).

[0017] Preferably, the volume ratio of the first solvent to the reducing agent is 1:(0.5-2).

[0018] More preferably, the volume ratio of the first solvent to the reducing agent is 1:1.

[0019] When the ratio of reducing agent to solvent is less than the minimum value mentioned above, the resulting nanowires become shorter. However, if the ratio is higher than the maximum value, the nanowires become thicker, more prone to agglomeration, and difficult to form a hollow morphology. Using this ratio is beneficial for achieving good uniform distribution in composite materials, ensuring the full utilization of precious metals.

[0020] According to some embodiments of the present invention, the mass-to-volume ratio of the tellurium source to the first solvent is 1:(1-10).

[0021] According to some embodiments of the present invention, the tellurium source is at least one selected from sodium tellurite, potassium tellurite, and telluric acid.

[0022] According to some embodiments of the present invention, the carbon source is at least one of glucose, starch, and cellulose.

[0023] The preparation method of this invention uses a green and environmentally friendly mild reducing agent, which greatly reduces the safety hazards in the experimental process compared with the traditional easily explosive chemical hydrazine hydrate, and also significantly reduces the pollution to the environment.

[0024] According to some embodiments of the present invention, the first solvent is water.

[0025] Preferably, the water is deionized water or distilled water.

[0026] According to some embodiments of the present invention, the stirring time is 0.5 to 3 hours.

[0027] According to some embodiments of the present invention, the stirring method is magnetic stirring or ultrasonic stirring.

[0028] According to some embodiments of the present invention, the heating temperature is 100-200°C.

[0029] According to some embodiments of the present invention, the heating time is 8 to 16 hours.

[0030] Compared to traditional heating methods, solvothermal heating is gentler, reduces energy consumption, and improves the quality and yield of tellurium nanowires.

[0031] When mixed with tellurium source in a reducing agent environment, the carbon source can act as both a surfactant and a reducing agent, preventing the tellurium source from agglomerating and resulting in excessively large precursor particles, which would be detrimental to the formation of nanoscale ruthenium telluride composite materials. In practice, after the tellurium source mixture is dissolved, the carbon source can be added, and the carbon source is simultaneously mixed. This can be achieved through methods such as stirring or ultrasonic vibration to ensure the carbon source is fully dissolved in the solvent and uniformly mixed with the dissolved tellurium source.

[0032] According to some embodiments of the present invention, the preparation method of the tellurium nanowire-supported noble metal composite material includes:

[0033] The precursor tellurium nanowires, the metal source, and the second solvent are mixed and stirred, heated to react, and the solid phase is separated to obtain a tellurium nanowire-supported noble metal composite material.

[0034] According to some embodiments of the present invention, the metal source is at least one selected from ruthenium trichloride, iridium trichloride, rhodium trichloride, chloroplatinic acid, gold chloride, and silver nitrate.

[0035] According to some embodiments of the present invention, the second solvent is at least one selected from ethylene glycol, ethanol, glycerol, isobutanol, and methanol.

[0036] According to some embodiments of the present invention, the mass ratio of the metal source to the precursor tellurium nanowire is 1:(0.5-3).

[0037] According to some embodiments of the present invention, the mass ratio of the metal source to the second solvent is 1:(1-3).

[0038] According to some embodiments of the present invention, the stirring time is 0.5 to 3 hours.

[0039] According to some embodiments of the present invention, the stirring method is magnetic stirring or ultrasonic stirring.

[0040] According to some embodiments of the present invention, the heating method is a solvothermal method.

[0041] According to some embodiments of the present invention, the heating temperature is 100-200°C.

[0042] According to some embodiments of the present invention, the heating time is 0.5 to 4 hours.

[0043] A second aspect of the present invention provides a tellurium nanowire-supported noble metal composite material, wherein the composite material is in the form of hollow strips.

[0044] The tellurium nanowire-supported noble metal composite material according to the second aspect of the present invention has at least the following beneficial effects:

[0045] The tellurium nanowire-supported noble metal composite material of this invention has relatively uniform particle size and low impurity content. It features a hollow structure, uniform morphology, and micropores on the surface, exhibiting a two-dimensional hollow potato-like shape. It possesses unique advantages in the field of electrocatalysis, increasing specific surface area and enhancing electrocatalytic activity. This not only improves material performance but also holds promise for its widespread application in areas such as electrocatalytic hydrogen evolution.

[0046] According to some embodiments of the present invention, the length of the composite material is 0.4 to 4 μm.

[0047] According to some embodiments of the present invention, the aspect ratio of the composite material is (2 to 20):1.

[0048] According to some embodiments of the present invention, the ratio of tellurium nanowires to loaded noble metal atoms is 1:2.

[0049] A third aspect of the present invention provides the application of the above-described tellurium nanowire-supported noble metal composite material and / or the tellurium nanowire-supported noble metal composite material prepared by the above-described preparation method in the field of hydrogen evolution catalysis.

[0050] The application of the third aspect of the present invention has at least the following beneficial effects:

[0051] This invention utilizes a green, mild, safe, and reliable preparation method to obtain a tellurium nanowire-supported noble metal composite material with high conductivity, uniform particle size distribution, large effective specific surface area, and a two-dimensional hollow potato-shaped structure, which can withstand current densities up to 10 mA cm⁻¹. -2 At this time, the overpotential is only 0.03V. This excellent electrocatalytic performance exhibits catalytic activity similar to that of platinum, and therefore it can be widely used in the field of catalysis.

[0052] According to some embodiments of the present invention, the catalytic field also includes other catalytic fields such as hydrogen evolution, hydrogenation, alcohol oxidation, and oxygen reduction.

[0053] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Attached Figure Description

[0054] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:

[0055] Figure 1 X-ray powder diffraction curves of tellurium nanowires and loaded noble metal composite materials prepared in the embodiments of the present invention;

[0056] Figure 2 The graph shows the effect of temperature on the XRD peak intensity of the tellurium nanowires prepared in Example 1 of this invention.

[0057] Figure 3 The image shows a 10.0 kx SEM image of the tellurium nanowires and the Ru / Rh / Ir / Pt composite material loaded with noble metals prepared in Example 1 of this invention.

[0058] (a) Tellurium nanowires; (b) Example 1; (c) Example 2; (d) Example 3; (e) Example 4

[0059] Figure 4 EDS images of tellurium nanowires and Ru / Rh / Ir / Pt composite materials loaded with noble metals prepared in the embodiments of the present invention;

[0060] (a) Tellurium nanowires; (b) Example 1; (c) Example 2; (d) Example 3; (e) Example 4;

[0061] Figure 5The polarization curves of the hydrogen evolution reaction are shown for the tellurium nanowires and the Ru / Rh / Ir / Pt composite material supported on noble metals prepared in Example 1 of this invention. Detailed Implementation

[0062] The embodiments of the present invention are described in detail below. Throughout the embodiments, the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0063] In the description of this invention, the use of terms such as "first," "second," etc., is for the purpose of distinguishing technical features only and should not be construed as indicating or implying relative importance, or implicitly indicating the number of technical features indicated, or implicitly indicating the order of the technical features indicated.

[0064] The terms "preferred," "more preferably," etc., used in this invention refer to embodiments of the invention that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this invention.

[0065] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0066] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of the present invention.

[0067] Unless otherwise specified, the reagents, methods and equipment used in this invention are all conventional reagents, methods and equipment in this technical field.

[0068] Example 1

[0069] This embodiment provides a method for preparing a tellurium nanowire-supported noble metal Ru composite material, including the following steps:

[0070] (1) Dissolve 100 mg potassium tellurite and 3 g glucose in 30 mL deionized water and 30 mL ethylene glycol, and stir until the potassium tellurite is completely dissolved to obtain the first mixed solution;

[0071] (2) The first mixed solution was placed in a reactor and reduced to tellurium nanowires under high temperature and high pressure. The heating temperature was 150℃ and the heating time was 12h; this was denoted as Te-150. Two control groups were also set up. (2.1) The first mixed solution was placed in a reactor and reduced to tellurium nanowires under high temperature and high pressure. The heating temperature was 120℃ and the heating time was 12h; this was denoted as Te-120. (2.2) The first mixed solution was placed in a reactor and reduced to tellurium nanowires under high temperature and high pressure. The heating temperature was 180℃ and the heating time was 12h; this was denoted as Te-180.

[0072] (3) Dissolve 10 mg of tellurium nanowires and 10 mg of ruthenium trichloride in 30 mL of ethylene glycol and stir until completely dissolved to obtain a second mixed solution;

[0073] (4) The second mixed solution is placed into a reaction vessel and subjected to high temperature and high pressure. The reduced noble metal ruthenium is attached to the tellurium nanowires. The heating temperature is 200℃ and the heating time is 2h to obtain the final product, tellurium nanowire loaded noble metal Ru composite material, denoted as RuTe@Te. There are some RuTe crystals on the surface of Te, which makes the electrocatalytic hydrogen evolution performance outstanding.

[0074] Example 2

[0075] This embodiment provides a method for preparing a tellurium nanowire-supported noble metal Pt composite material, including the following steps:

[0076] (1) Dissolve 100 mg potassium tellurite and 3 g glucose in 30 mL deionized water and 30 mL ethylene glycol, and stir until the potassium tellurite is completely dissolved to obtain the first mixed solution;

[0077] (2) The first mixed solution was placed into a reaction vessel and reduced to tellurium nanowires under high temperature and high pressure. The heating temperature was 150°C and the heating time was 12h.

[0078] (3) Dissolve 10 mg of tellurium nanowires and 10 mg of chloroplatinic acid in 30 mL of ethylene glycol and stir until completely dissolved to obtain a second mixed solution;

[0079] (4) The second mixed solution is placed into a reaction vessel and subjected to high temperature and high pressure. The reduced noble metal rhodium is attached to the tellurium nanowires. The heating temperature is 200℃ and the heating time is 2h to obtain the final product, tellurium nanowire loaded noble metal Rh composite material, denoted as RhTe@Te.

[0080] Example 3

[0081] This embodiment provides a method for preparing a tellurium nanowire-supported noble metal Rh composite material, including the following steps:

[0082] (1) Dissolve 100 mg potassium tellurite and 3 g glucose in 30 mL deionized water and 30 mL ethylene glycol, and stir until the potassium tellurite is completely dissolved to obtain the first mixed solution;

[0083] (2) The first mixed solution was placed into a reaction vessel and reduced to tellurium nanowires under high temperature and high pressure. The heating temperature was 150°C and the heating time was 12h.

[0084] (3) Dissolve 10 mg of tellurium nanowires and 10 mg of rhodium trichloride in 30 mL of ethylene glycol and stir until completely dissolved to obtain a second mixed solution;

[0085] (4) The second mixed solution is placed into a reaction vessel and subjected to high temperature and high pressure. The reduced noble metal platinum is attached to the tellurium nanowires. The heating temperature is 200℃ and the heating time is 2h to obtain the final product, tellurium nanowire loaded noble metal Pt composite material, denoted as PtTe@Te.

[0086] Example 4

[0087] This embodiment provides a method for preparing tellurium nanowire-supported noble metal Ir composite material, including the following steps:

[0088] (1) Dissolve 100 mg potassium tellurite and 3 g glucose in 30 mL deionized water and 30 mL ethylene glycol, and stir until the potassium tellurite is completely dissolved to obtain the first mixed solution;

[0089] (2) The first mixed solution was placed into a reaction vessel and reduced to tellurium nanowires under high temperature and high pressure. The heating temperature was 150°C and the heating time was 12h.

[0090] (3) Dissolve 10 mg of tellurium nanowires and 10 mg of iridium trichloride in 30 mL of ethylene glycol and stir until completely dissolved to obtain a second mixed solution;

[0091] (4) The second mixed solution is placed into a reaction vessel and subjected to high temperature and high pressure. The reduced noble metal iridium is attached to the tellurium nanowires. The heating temperature is 200℃ and the heating time is 2h to obtain the final product, tellurium nanowire loaded noble metal Ir composite material, denoted as IrTe@Te.

[0092] Test case

[0093] The product obtained in Example 1 was subjected to corresponding performance tests, including X-ray powder diffraction (XRD), scanning electron microscopy (SEM), electron energy distribution (EDS), and hydrogen evolution performance testing.

[0094] (I) XRD Test

[0095] The final product was tested according to standard XRD testing procedures, and the test results are as follows: Figure 1 As shown. Figure 1 A comparison of the aforementioned spectrum with the standard diffraction peak spectrum PDF#36-1452 shows that the XRD diffraction peaks of the RuTe@Te composite material synthesized by this method correspond to the standard spectrum, proving that the final product obtained in Example 1 of this invention is a RuTe@Te composite material. Figure 2 This indicates that the appropriate temperature has different effects on the XRD peak intensity of the Te nanowire support material. At 150℃, the tellurium nanowires exhibit a larger peak intensity, thus demonstrating better crystallinity.

[0096] (II) SEM Testing and EDS Testing

[0097] Following standard SEM scanning procedures, the final product of Example 1 was subjected to SEM scanning tests. The preparation method of Example 1 yielded a hollow potato-shaped final product with uniform morphology. Numerous micropores were observed on the surface of the hollow potato-shaped product. Combining the XRD and SEM results, it can be concluded that Example 1 of this invention obtained a nanoscale RuTe@Te composite material. Specific test results are as follows... Figure 3 As shown.

[0098] EDS scanning was performed on the final product of Example 1. Ru and Te were uniformly distributed on the nanowires. The specific results are as follows: Figure 4 As shown.

[0099] (III) Catalytic hydrogen evolution test

[0100] Following conventional methods, the nano-RuTe@Te composite material obtained in Example 1 was used for the hydrogen evolution reaction, and its polarization curve was tested. Specific test results are as follows: Figure 5 As shown.

[0101] from Figure 5 It can be seen that in Embodiment 1 of the present invention, when the current density is 10 mA cm⁻¹ -2 At that time, the overpotential was only 0.03V, and when the current density was 10mA cm⁻¹ -2 At that time, the overpotentials of the nano-RuTe@Te, IrTe@Te, RhTe@Te, and PtTe@Te composite materials obtained in Examples 2 to 5 were 27, 30.7, 31.2, and 34.1 mV, respectively. It can be seen that the hydrogen evolution performance of the nano-composite materials obtained in the examples of the present invention all exceed the hydrogen evolution reaction catalytic performance of the noble metal Pt (34.4 mV).

[0102] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.

Claims

1. A method for preparing precursor tellurium nanowires, characterized in that, The method for preparing the precursor tellurium nanowires includes the following steps: Tellurium source, carbon source, reducing agent and first solvent are mixed and stirred, heated to react, and the solid phase is separated to obtain precursor tellurium nanowires; The reducing agent is ethylene glycol or sodium citrate; The mass ratio of the tellurium source to the carbon source is 1:(1~40). The volume ratio of the first solvent to the reducing agent is 1:(0.25~3); The mass-to-volume ratio of the tellurium source to the solvent is 1:(100~1000)g / mL; The tellurium source is at least one of sodium tellurite, potassium tellurite, and telluric acid. The carbon source is at least one of glucose, starch, and cellulose; The first solvent is water.

2. The preparation method according to claim 1, characterized in that, The stirring time is 0.5~3h.

3. The preparation method according to claim 1, characterized in that, The stirring method is magnetic stirring or ultrasonic stirring.

4. The preparation method according to claim 1, characterized in that, The heating temperature is 100~200℃.

5. The preparation method according to claim 1, characterized in that, The heating time is 8 to 16 hours.

6. A method for preparing a tellurium nanowire-supported noble metal composite material, characterized in that, Includes the following steps: The precursor tellurium nanowires, the metal source, and the second solvent were mixed and stirred, heated to react, and the solid phase was separated to obtain a tellurium nanowire-supported noble metal composite material. The precursor tellurium nanowires are prepared by the preparation method according to any one of claims 1 to 5.

7. The preparation method according to claim 6, characterized in that, The metal source is at least one of ruthenium trichloride, iridium trichloride, rhodium trichloride, chloroplatinic acid, gold chloride, and silver nitrate.

8. The preparation method according to claim 6, characterized in that, The second solvent is at least one of ethylene glycol, ethanol, glycerol, isobutanol, and methanol.

9. The preparation method according to claim 6, characterized in that, The mass ratio of the metal source to the precursor tellurium nanowires is 1:(0.5~3).

10. The preparation method according to claim 6, characterized in that, The mass-to-volume ratio of the metal source to the second solvent is 1:(1~3)mg / mL.

11. The preparation method according to claim 6, characterized in that, The stirring time is 0.5~3h.

12. The preparation method according to claim 6, characterized in that, The stirring method is magnetic stirring or ultrasonic stirring.

13. The preparation method according to claim 6, characterized in that, The heating method is a solvothermal method.

14. The preparation method according to claim 6, characterized in that, The heating temperature is 100~200℃.

15. The preparation method according to claim 6, characterized in that, The heating time is 0.5 to 4 hours.

16. A tellurium nanowire-supported noble metal composite material prepared by the preparation method according to any one of claims 6 to 15, characterized in that, The composite material is in the form of hollow strips.

17. The tellurium nanowire-supported noble metal composite material according to claim 16, characterized in that, The length of the composite material is 0.4~4μm.

18. The tellurium nanowire-supported noble metal composite material according to claim 16, characterized in that, The aspect ratio of the composite material is (2~20):

1.

19. The tellurium nanowire-supported noble metal composite material according to claim 16, characterized in that, The ratio of tellurium nanowires to loaded noble metal atoms is 1:

2.

20. The application of a tellurium nanowire-supported noble metal composite material prepared by the preparation method according to any one of claims 6 to 15 in the field of fuel cell catalysis.

Citation Information

Patent Citations

  • Bi2Te3-Sb2Te3 core-shell structure nanometer wire and preparing method thereof

    CN105382254A

  • Formic acid hydrogen production catalyst and preparation method and application thereof

    CN110026213A

  • Tellurium nanowire as well as synthesis method and application thereof

    CN113307234A